Determinants of continuance usage intentions: the mediating role of satisfaction and trust in branded mobile applications among Malaysians - Sharlini Seridaran; Arumugam G. Sithamparam; Mohammad Falahat; Ömer Ekmekcioğlu (Cogent Business & Management, 2024)
This research aims to examine the determinants of continuance usage intentions influence comprises customer engagement, electronic word-of-mouth (e-WOM), technology self-efficacy, personalization, user interface, and reward system on the continuance usage intention of branded mobile applications among Malaysians, with a focus on the mediating roles of customer satisfaction and trust. Employing a quantitative research design, the study gathered data from 430 respondents via an online survey. The data analysis was conducted using Smart Partial Least Squares (Smart PLS) to evaluate the impact of the independent variables on continuance usage intention, alongside the mediating effects of customer satisfaction and trust. The results revealed that all independent variables, except for the reward system, significantly influence continuance usage intention. Moreover, while customer satisfaction was found to mediate the relationship between all independent variables and continuance usage intention positively, customer trust did not mediate the effect of customer engagement and personalization on continuance usage intention. This study contributes to the limited literature on the continuance usage of branded mobile applications, particularly in the context of developing economies. It highlights the importance of customer engagement, e-WOM content, technology self-efficacy, personalization, and user interface in fostering continuance usage intention. Additionally, it underscores the differential mediating roles of customer satisfaction and trust, providing valuable insights for researchers and practitioners aiming to enhance the continuance usage of branded mobile applications.
Keywords: 650; Continuance usage; customer engagement; e-WOM content; technology self-efficacy